2020
DOI: 10.1039/d0sc02503h
|View full text |Cite
|
Sign up to set email alerts
|

Elusive structural changes of New Delhi metallo-β-lactamase revealed by ultraviolet photodissociation mass spectrometry

Abstract: We use mass spectrometry (MS), under denaturing and non-denaturing solution conditions, along with ultraviolet photodissociation (UVPD) to characterize structural variations in New Delhi metallo-β-lactamase (NDM) upon perturbation by ligands or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…In this study, the ramifications of secondary, tertiary, and quaternary structure were not integrated into the analysis in order to evaluate patterns based solely on absolute identities of the amino acids for a large collection of proteins in a variety of charge states. Other prior studies of native-like proteins by UVPD have considered the impact of higher-order structural features, mainly in the context of rationalizing changes in fragmentation propensities for pairs or sets of apo versus holo proteins. An extensive statistical analysis of the influence of secondary, tertiary, and quaternary structural factors is underway and will be presented separately. Data in the present study was amassed from previous and new data sets collected using UVPD-enabled Orbitrap platforms based on the analysis of sequence fragments (i.e., N-terminal and C-terminal containing ions from backbone cleavages) from 38 protein molecular ions encompassing 28 proteins and different charge, ligation, and oligomeric states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the ramifications of secondary, tertiary, and quaternary structure were not integrated into the analysis in order to evaluate patterns based solely on absolute identities of the amino acids for a large collection of proteins in a variety of charge states. Other prior studies of native-like proteins by UVPD have considered the impact of higher-order structural features, mainly in the context of rationalizing changes in fragmentation propensities for pairs or sets of apo versus holo proteins. An extensive statistical analysis of the influence of secondary, tertiary, and quaternary structural factors is underway and will be presented separately. Data in the present study was amassed from previous and new data sets collected using UVPD-enabled Orbitrap platforms based on the analysis of sequence fragments (i.e., N-terminal and C-terminal containing ions from backbone cleavages) from 38 protein molecular ions encompassing 28 proteins and different charge, ligation, and oligomeric states.…”
Section: Resultsmentioning
confidence: 99%
“…Akin to some of the features of ExD methods, 193 nm UVPD cleaves covalent bonds in the protein backbone while preserving noncovalent interactions, as evidenced by the detection of holo product ions that retain bound ligands . By capitalizing on this finding, ligand binding sites have been localized based on mapping the absence and presence of holo product ions. Results from several studies have indicated that the propensity of backbone cleavages throughout the protein is mediated by the flexibility of the region, conformational changes, and engagement in noncovalent interactions, all of which modulate the release of detectable fragment ions. UVPD has also been extended to the examination of multimeric protein assemblies, for which ejection of subcomplexes and monomeric subunits reveal subunit connectivity and stoichiometry. ,, In sum, native-top down UVPD is sensitive to quaternary, tertiary, and secondary structure, providing an intriguing opportunity to expand its application in the field of structural biology.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of carbapenem hydrolysis catalyzed by serine carbapenemase (A), B1/B3 metallo-carbapenemase (B) and B2 metallo-carbapenemase (C). ,, …”
Section: Catalytic Mechanisms Of Different Carbapenemasesmentioning
confidence: 99%
“…80,81 Prior UVPD studies of other protein-ligand complexes have either not observed fragmentation of the ligand, as the amide backbone of the protein is a signicant UV chromophore, or have not undertaken searches for fragment ions containing sub-portions of the ligands owing to the enormous search space and potential for false positives. 52,60,70,71,82,83 In essence, considering only holo fragment ions which contain the entire mass of the ssDNA ligand may exclude the identication of some meaningful ions but importantly avoids increasing the false positive rate for identication of misassigned spurious holo fragment ions.…”
Section: Resultsmentioning
confidence: 99%